Evaluation of the design effects of different agropastoral systems on the diversity and density of spiders - Almada, Melina S.; González, Alda; Corronca, José A. (Spanish Journal of Agricultural Research, 2017)
Sustainable agro-ecological design is challenging when the goal is self-regulation of the system. The objective of this study was to evaluate if the agropastoral design system affects the spider community, as spiders are the main predators in these production systems, and to determine those designs which maximize the diversity and density of spiders. The study was conducted during 2009/2010, at the Experimental Research Station of Agriculture (EEA-INTA) Reconquista (Santa Fe, Argentina) where we considered four different designs: C1 (five agricultural fields), C2 (three agricultural fields and four livestock fields), C3 (six agricultural fields and one livestock field) and C4 (five agricultural fields and one forest area). In each design, the spiders were collected by pitfall traps and suction samples with a G-Vac (garden-vacuum). The designs proposed were considered on the basis of environmental heterogeneity. The C4 treatment had the greatest number of species, followed by C2, C3 and C1 (183, 178, 144 and 142 species, respectively), and C2 presented the greatest abundance of spiders followed by C4, C3 and C1 (n=5708, 4785, 4271 and 3448, respectively). Eight guilds were present in C3 and C4. This study is the first to evaluate the diversity of spiders in agropastoral systems in Argentina. Our results show that designs that include more fields with livestock or equal to those for agriculture, as well as forest areas, increase environmental heterogeneity. Therefore, the presence of a biological controller and dominant predatory group will be possible with sustainable designs that have environmental heterogeneity, contributing to improved pest control in agricultural systems.